2017
DOI: 10.1016/j.talanta.2017.05.081
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of mercury speciation in feathers using species-specific isotope dilution analysis

Abstract: Seabirds are considered as effective sentinels of environmental marine contamination and their feathers are extensively used as non-lethal samples for contaminant biomonitoring. This tissue represents the main route for mercury (Hg) elimination in seabirds and contains predominantly methylmercury (MeHg). In this work, we developed a robust analytical technique for precise and accurate simultaneous quantification of MeHg, inorganic Hg (iHg) and consequently total Hg (THg), in feathers by gas-chromatography (GC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 45 publications
2
28
0
2
Order By: Relevance
“…Hence, BF collected from 2007 to 2016 were analyzed for comparison with the biological time-series. Previous studies showed that >90% of Hg in seabird feathers is methyl-Hg (Me-Hg), the most toxic form of Hg 95 . Total Hg measured in feathers is thus considered as an indicator of bird exposure to Me-Hg.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, BF collected from 2007 to 2016 were analyzed for comparison with the biological time-series. Previous studies showed that >90% of Hg in seabird feathers is methyl-Hg (Me-Hg), the most toxic form of Hg 95 . Total Hg measured in feathers is thus considered as an indicator of bird exposure to Me-Hg.…”
Section: Methodsmentioning
confidence: 99%
“…The extraction was carried out in CEM Pyrex vessels by 1 min of warming up to 75ÂșC and 3 min at 75ÂșC with magnetic agitation to homogenise the samples. Feathers (~ 100 mg dry weight (dw)) were digested using nitric acid (HNO3‱6N, INSTRA quality) with addition of isotopic enriched standard solutions before the extraction process following Renedo et al (2017). Blood and internal tissues (100-150 mg dw) were digested with 5 mL of tetramethylammonium hydroxide (25% TMAH in H2O, Sigma Aldrich).…”
Section: Hg Speciation Analysismentioning
confidence: 99%
“…Gradual decrease of Hg concentrations in seabird internal tissues during feather moult was identified as remobilisation of Hg body burden into growing feathers, leading to the elimination of up to 80% of the total accumulated Hg (Furness et al, 1986;Honda et al, 1986;Braune, 1987). Since relatively high Hg concentrations (almost exclusively MeHg) are usually measured in feathers (Renedo et al, 2017), the feather moult is considered as the main route for MeHg elimination in seabirds (Thompson and Furness, 1989a;Thompson et al, 1990). However, the evidence of excretion of MeHg by feathers is based simply on the balance of Hg concentrations between feathers and internal tissues, while the relative importance of the different soft tissues in the storage and distribution of Hg is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to Hg speciation analyses, blood and feathers (0.01−0.05 g) were digested following a previously developed method by microwave-assisted extraction (using a Discover SP-D microwave, CEM Corporation) 55,56 . We used 5 mL of tetramethylammonium (Table S1).…”
Section: Sample Preparation Analyses Of Total Hg and Hg Species Concmentioning
confidence: 99%